Empowering University Students with Cutting-Edge True Wireless Stereo Selection: A Comparative Analysis of Simple Additive Weighting and TOPSIS Algorithms - Oetama, Raymond (The Indonesian Journal of Computer Science, 2024)
Currently, there are a lot of Solid-State Drives or SSDs that are running in the market. Each SSD can come with different features and prices from one another. Hence, this can confuse buyers planning to purchase one for their PC or laptop. It also applies to university students who depend on laptops to do college work and run on a limited budget. Any mistake in deciding which SSD to use can be costly. Henceforth, this paper aims to help decide what SSD would be best for an average university student. Two algorithms will determine which SSDs are best for university students to buy. The algorithms used are Simple Additive Weighting and Technique for Order of Preference by Similarity to Ideal Solution. The results of these algorithms are used to show the top three best SSDs for university students. Therefore, university students can make an informed choice based on the results from both algorithms.